Protein Haemaglutinin Outer Membran Protein (OMP) 35 kDa sebagai Protein Adhesin Proteus mirabilis pada Vesika Urinaria Kelinci - Suswati, Enny; Mufida, Diana Chusna (Jurnal Natur Indonesia, 2010)
Proteus mirabilis is opportunistic and nosocomial pathogen that usually found in clinical specimen from patientswith catheter. The pathogenic mechanism of the bacteria are not fully elucidated especially its potential activity ofthe protein as hemaglutinin and adhesion molecule. The aim of this study is to evaluate the role of 35 kDa outermembrane protein from P. mirabilis. After identification, bacterial isolate of OMP fraction 12,5% SDS-PAGE wereused to isolate OMP followed by hemaglutinin test and invitro adhesion test. The study showed that the 35 kDa OMPof P. mirabilis was a hemaglutinin protein that could agglutinate mice erythrocytes, rabbit erythrocytes, and humangroup O erythrocytes. Hemaglutination test were negative on erythrocytes human blood group A,B, and AB. The 35kDa OMP was also adhesion protein showed by its activity to adhere to the rabbit vesica urinaria epithel receptor.The increase dose of 35 kDa OMP will decrease the amount of P. mirabilis bacteria to adhere to rabbit vesicaurinaria epithel (p< 0,05 ).